LINKING HUMAN RIGHTS WITH ENVIRONMENT TOWARDS SUSTAINABILITY: EXPLORING THE UNADDRESSED CONCERNS FROM INDIAN ENVIRONMENTAL PERSPECTIVES - BHATTACHARYA, DR. BHUPAL (International Journal of Advanced Science and Technology, 2019)
The issues of sustainable development have received great importance in protecting the conditions of environment. The urgent requirement of present day is properly monitoring the implementation measures for pollution control and tackling environmental problems.It is essential that the developmental phase for this new century should be more conscious of creating a long-term negative impact on environment connecting the conditions of environment with Human Rights Unclear and adoption of weak words in the enactment, results into favouring the violator in flouting out the objects and intentions of the Parliament. During the present days of crisis use of natural resources are rampant. Every nation to a larger extent gives priority to its development as they are directly linked with finance and earnings of more Gross Domestic Product which is the considered as the parameter for measuring the progress and growth of nation.